The business of childcare in Europe - Penn, Helen (European early childhood education research journal, 2014)
This article is based on work undertaken for the European Commission (EC) as part of a wider project on what is termed 'social services of general interest'. The EC is currently engaged in considering what kind of legislative and quality assurance mechanisms might be promoted for those social services, which have been opened up to competition. The EC work reported here mapped the extent to which early education and childcare (ECEC) is provided by private organizations in the member states of the European Union, and what regulatory frameworks exist for such services. This article foregrounds the situation in the UK, and England in particular. England is exceptional in Europe in the degree to which it has conceptualized and promoted childcare as a business or for-profit enterprise; and it has developed a regulatory framework with a narrow scope which excludes or limits such issues as financial regulation, access, pay and conditions of work for staff, and accountability measures.